Cultural Capital Information Management and Sustainability in the Context of Thailand Local Government Organizations - Anontachai, Chatkamon; Tuamsuk, Kulthida; Chansanam, Wirapong (Journal of Posthumanism, 2025)
Cultural capital information management plays a vital role in supporting sustainable development in several ways. The research aims to study cultural capital information management to promote sustainable development within the scope of the Local Administration Organizations (LAOs)’ roles and responsibilities. Qualitative research methods are employed to obtain data from individuals involved in managing and practicing cultural aspects of the community. The researchers chose the province of Roi Et as the study area because it is historically significant with ancient communities deeply rooted in cultural heritage. The main data providers for this research included cultural administrators and practitioners working in LAOs, a total of 15 individuals selected according to the criteria. Data collection involved in-depth interviews and document content analysis. The findings are presented on three main points: (1) the roles and responsibilities of LAOs in cultural capital; (2) cultural capital information management by the LAOs; and (3) cultural capital information management in the aspects of sustainable development including education and learning, community engagement, and cultural heritage conservation. Understanding the context of LAOs in cultural information management linked to sustainable development is valuable for academics, researchers in library and information science, and practitioners involved in LAOs. It also provides insights for designing and developing community information systems for sustainable cultural capital management.